Analysis of the Principles of Trust and Fund Accounting in Encouraging Transparency and Accountability in Zakat Management: A Case Study of BAZNAS Medan - Diah Hanifah Daulay; Juliana Nasution; Nur Ahmadi Bi Rahmani (Indonesian Journal of Islamic Economics and Finance, 2026)
This study examines the integration of the amanah principle and Fund Accounting in enhancing transparency, accountability, and public trust in zakat management at BAZNAS Medan. Using a qualitative case study approach, data were collected through in-depth interviews, observations, and documentation, then analyzed using the Miles and Huberman model with source and method triangulation to ensure validity. The findings reveal that the amanah principle is implemented not only as a moral and spiritual value but also through institutional practices, including strict standard operating procedures, dual control mechanisms, internal audits, and transparent reporting. Transparency is applied gradually, with some reports published online and others provided upon formal request. The implementation of Fund Accounting enables the clear separation of zakat, infaq, sadaqah, amil, and other social funds in accordance with PSAK 109, PSAK 401 and PSAK 409, thereby strengthening financial accountability. The synergy between amanah and Fund Accounting has increased muzakki trust, improved financial supervision, and supported the effectiveness of zakat distribution programs in enhancing mustahik welfare. Although challenges remain in human resources and information technology, BAZNAS Medan demonstrates good zakat governance. Nevertheless, the study identifies a critical transparency gap, wherein the tiered disclosure policy requiring formal requests for certain financial reports represents an institutional limitation that constrains the achievement of full public trust and demands strategic digitalization to bridge the gap between procedural accountability and substantive transparency in the modern era.